(untitled) (MAUSAM, 1980)
A simple conceptual model of water transport in the unsaturated soil zone is presented. The transport of water is visualized in pulses of infiltrating sheet through a series of inter-connected expandable mixing cells. By applying mass balance equation, successively to each hypothetical mixing cell sub-dividing the soil profile, at discrete time intervals, the process of dispersion and mixing during transport of water through the unsaturated zone is mathematically approximated. Simulation of tritium tracing experiments in Indo-Gangetic plains of north India, using the above model, is shown to closely reproduce the field data. A close correlation is seen to exist between the rainfall and the estimated number of recharge pulses from the field data.